Mechanical Characteristics and Energy Evolution of Sandstone Three-Point Bending Test - Tao Qin; Kai Ren; Zhi Liu; Yan-Wei Duan; Lei Wang (Shock and Vibration)
With the increase of underground mining depth in coal mines, the distribution of stress fields in deep mining becomes more complex, and the stress localization characteristics are obvious. In order to obtain the local mechanical properties and energy evolution of sandstone, this article is based on the three-point bending experiment and combined with the localized failure theory to explore the evolution law of stress field, deformation field, and energy field of sandstone specimen under tensile stress during the three-point bending experiment. The results show that during the three-point bending test of sandstone, with the increase of the span of the three-point bending test, the peak stress at the characteristic point shows an increasing trend, and the peak stress has obvious regional characteristics. In the vertical direction, the peak stress at the characteristic points in the upper part of the neutral layer is larger, and the peak stress at the characteristic points in the lower part of the neutral layer is smaller. In the horizontal direction, the peak stress at the characteristic points in the near field is higher, and the peak stress at the characteristic points in the middle field and the far field is smaller. The stress field and the deformation field have a good corresponding relationship. The upper far-field peak strain tends to decrease with the increase of the span, and the upper near-field peak strain first decreases and then increases with the increase of the span. The lower near-field peak strain tends to decrease and then increase with increasing span, and the lower far-field peak strain fluctuates with increasing span. The energy field is dependent on the stress field and the deformation field, showing obvious regional characteristics. The energy storage and release capacity of the upper area are higher than those of the lower area. The overall performance of the loading energy storage, rebound energy release, and crack propagation energy release in different areas can be described as far field < mid-field << near field. The near-field energy at different spans presents the characteristics of two stages. When the span is between 140 mm and 150 mm, the near-field energy shows a rapid decreasing trend, and when the span is between 150 mm and 180 mm, the near-field energy presents an obvious increasing trend.